Effectiveness of DLSU pure online integrating courses in the CPA board exam performance during the pandemic period - Asuncion, Stephanie Ann M. (Animo Repository, 2023)
During the COVID-19 pandemic, educational institutions quickly shifted to online learning. This study investigated the effect of DLSU's pure online integrating courses on the graduates’ CPA board exam performance. Through an examination of the curriculum aspects and a review of relevant literature, the researchers found possible causal links between integrating courses and passing the board exam. Notably, the country's CPA board exam passing rate as well as HEIs' performance rating have decreased during the pandemic. Given the limitations of existing studies, the researchers used a causal research design and purposive sampling to offer fresh insights on the topic. Lasallian CPAs who had undergone pure online integrating courses and passed the board exam during the pandemic period were surveyed to gain a comprehensive understanding of their experiences. The study findings indicated that INTMANS was perceived as the most helpful course, while INTSBUSL was considered the least helpful. Respondents had positive evaluations of the coverage, materials, faculty, delivery, and assessment of the courses. However, further analysis revealed that among the identified curriculum aspects, only coverage and faculty have significant effects on CPA board exam performance. Ultimately, the study concluded that pure online integrating courses did not have a significant effect on the CPA board exam performance. Professor support and asynchronous learning were among the strengths attributed to those courses, while time inadequacy was highlighted as a major weakness. Overall, these findings contributed to existing literature and emphasized the importance of further research on factors influencing CPA board exam success in an online learning environment.